(untitled) (Diametros, 2014)
This paper offers a critical discussion of Jonathan Israel’s thesis that the political and moral ideas and values which define liberal democratic modernity should be regarded as the legacy of the Radical Enlightenment and thus as deriving from Spinoza. What I take issue with is not Israel’s map of the actual historical lines of intellectual descent of ideas and account of their social and political impact, but the accompanying conceptual claim, that Spinozism as filtrated by the naturalistic wing of eighteenth-century French thought, is conceptually sufficient for the ideology of modernity. The post-Kantian idealist development, I argue, qualifies as radical, and hinges on Spinoza, but its construal of Spinoza does not fit Israel’s thesis, and reflects an appreciation of the limitations, for the purpose of creating a rational modernity, of the naturalistic standpoint represented by thinkers such as d’Holbach.